Accelerated ambulation after vascular access closure device. (May 2018) - Brancheau, Daniel; Sarsam, Sinan; Assaad, Mahmoud; Zughaib, Marcel
Background: Patients who are candidates to receive an Angioseal® (St. Jude Medical) device for arteriotomy closure are allowed to ambulate 20 min after the deployment of the device. More frequently, however, patients are kept on bed rest for several hours following Angioseal® deployment. The purpose of this study was to prospectively assess patients when ambulating 20 min after Angioseal® deployment instead of prolonged best rest of 2–3 h. Methods: Patients undergoing angiography from the common femoral artery approach were included in the study if they received a 6 Fr Angioseal® closure device. Results: Twenty-nine patients were successfully enrolled in the study; 27 (93.1%) patients ambulated at 20 min, 1 (3.45%) patient ambulated at 28 min, and 1 (3.45%) patient ambulated at 27 min due to transport times. There were zero complications with regard to hemorrhage or other groin complications. There is a substantial time difference in ambulation times between the conventional and early ambulation groups. Conclusion: Our study demonstrates that it is probably safe to ambulate patients who undergo diagnostic cardiac catheterization as early as 20 min after deployment of the 6 Fr Angioseal® closure device. ClinicalTrials.gov identifier: NCT03142126